2022
DOI: 10.3389/fimmu.2022.985622
|View full text |Cite
|
Sign up to set email alerts
|

When liquid-liquid phase separation meets viral infections

Abstract: Eukaryotic cells have both membranous and membraneless organelles. While the formation mechanism of membranous organelles is well understood, the formation mechanism of membraneless organelles remains unknown. Many biomolecules in the cytoplasm transition from the liquid phase to the agglutinated phase are known as liquid-liquid phase separation (LLPS). The biomolecular agglomerates’ physical properties enable them to function as dynamic compartments that respond to external pressures and stimuli. Scientists h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…It has been increasingly appreciated that BMCs play an important role the replication of many viruses, including influenza, SARS-CoV-2, HIV-1, and others, as reviewed elsewhere [81][82][83][84]. In our previous work, we observed the in vivo formation of RSV Gag foci in the nucleus, cytoplasm, and plasma membrane that colocalize with unspliced viral RNA and splicing factors [3,4,23].…”
Section: Discussionmentioning
confidence: 71%
“…It has been increasingly appreciated that BMCs play an important role the replication of many viruses, including influenza, SARS-CoV-2, HIV-1, and others, as reviewed elsewhere [81][82][83][84]. In our previous work, we observed the in vivo formation of RSV Gag foci in the nucleus, cytoplasm, and plasma membrane that colocalize with unspliced viral RNA and splicing factors [3,4,23].…”
Section: Discussionmentioning
confidence: 71%
“…These factories are membraneless structures that have biophysical properties of biomolecular condensates, and emerging evidence suggests that some are nucleated via the process of LLPS ( 40 , 41 ). Hallmarks of LLPS are the formation of spherical droplets through phase separation of proteins and/or nucleic acid ( 42 ). The droplets are dynamic and fuse together over time, allowing the virus to accumulate and consolidate needed resources ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hallmarks of LLPS are the formation of spherical droplets through phase separation of proteins and/or nucleic acid ( 42 ). The droplets are dynamic and fuse together over time, allowing the virus to accumulate and consolidate needed resources ( 42 ). Indeed, it has been shown that RV viroplasms are biomolecular condensates formed in part by the phase separation of non-structural proteins NSP2 and NSP5 ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LLPS provides an excellent solution to the problem of physical and functional separation of viral macromolecules from those endogenous to the host cell in its cytosol. Accordingly, LLPS has emerged as a new promising target for antiviral approaches [23][24][25].…”
Section: Introductionmentioning
confidence: 99%